2006
DOI: 10.1111/j.1574-6941.1997.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Glyceria maxima and nitrate input on the composition and nitrate metabolism of the dissimilatory nitrate-reducing bacterial community

Abstract: The influence of nitrate addition and the presence of Glyceria maxima (reed sweetgrass) on the composition and nitrate metabolism of the dissimilatory nitrate‐reducing bacterial community was investigated. Anoxic freshwater sediment was incubated in pots with or without G. maxima and with or without addition of nitrate. After incubation the sediments were sampled. Dilution series of these sediment samples were incubated in deep agar tubes and almost all colonies from the most diluted tubes were isolated and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Corre and co-workers [13] suggested a high competition for available N between microorganisms and plant. Moreover, Nijburg and co-workers [37,38] noticed that addition of nitrate in the rhizosphere of G. maxima resulted in an increased number of NR strains. In order to test the role of nitrate availability, a similar experiment was conducted on L. perenne grown with low and high (non-limitative) nitrogen supply, during which the role of nitrate availability was confirmed (L. RousselDelif, S. Tarnawski, J. Hamelin, E.M. Baggs, M. Aragno, and N. Fromin, in preparation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corre and co-workers [13] suggested a high competition for available N between microorganisms and plant. Moreover, Nijburg and co-workers [37,38] noticed that addition of nitrate in the rhizosphere of G. maxima resulted in an increased number of NR strains. In order to test the role of nitrate availability, a similar experiment was conducted on L. perenne grown with low and high (non-limitative) nitrogen supply, during which the role of nitrate availability was confirmed (L. RousselDelif, S. Tarnawski, J. Hamelin, E.M. Baggs, M. Aragno, and N. Fromin, in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ability to use nitrate as alternative electron acceptor could be a competitive advantage for bacteria in the rhizosphere, where oxygen is limiting because of root and microbial respiration [21]. In contrast, Nijburg and co-workers [37,38] reported a lower proportion of nitrate-reducing bacterial isolates in the rhizosphere of the aerenchymatous wetland plant Glyceria maxima compared to nonrhizospheric soil, suggesting that the availability of nitrate is also crucial for nitrate dissimilation. Various studies showed that denitrification in soil is also influenced by soil properties and agricultural practices [9,12,17,40,54].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of certain macrophytes in low nitrate sediments may greatly increase the proportion of DNRA to denitrification, possibly due to increased C availability from root exudates and elevated O 2 levels, (Nijburg & Laanbroek 1997b). Aerenchymatous plants release O 2 into the root zone when healthy (Nijburg et al 1997), and this process in turn selects for DNRA over denitrification as DNRA is less inhibited by O 2 presence than denitrification, especially at high C:N ratios (Fazzolari et al 1998). Potamogeton praelongus and Elodea canadensis (identified as aerenchymatous macrophytes) were abundant in Bull Trout Lake and were present at Site 5.…”
Section: Spatial Patterns In No 3 − Losses By Dissimilatory Pathwaysmentioning
confidence: 99%
“…Under flooding, nitrate replaces oxygen as the terminal electron acceptor in microbial respiration leading to denitrification and/ or nitrate ammonification [23]. In fact, three nitrate reducing pathways are known in soils: (1) dissimilatory nitrate reduction to ammonia (DNRA or accumulators), (2) nitrogen dissimilating bacteria which are only able to reduce nitrate to nitrite ( accumulators) and (3) denitrifyiers that are able to reduce nitrate to nitrous oxide or to dinitrogen [5,7,27]. Bacterial reduction of nitrate is considered to be an important loss of available nitrogen from soils [3,19].…”
Section: Introductionmentioning
confidence: 99%